Role of WOM, Green Marketing, Environmental Knowledge on Purchase Intention : Mediated Role of Attitude - Adlani, Muhammad faisal; Asih, Daru (International Journal of Indonesian Business Review, 2025)
Purpose – This research focuses on the phenomenon of environmental sustainability, especially in the context of air pollution due to motor vehicle emissions in DKI Jakarta. This study aims to analyse the effect of word of mouth, green marketing, environmental knowledge on purchase intention mediated by attitudes in electric GrabBike customers. Methodology/approach – The research design used is quantitative descriptive research using the total population of 168 respondents. Data analysis using the Smart PLS 4.0 application which consists of testing the inner model and outer model. Findings – It The results found that Green Marketing has a positive and significant impact on Attitudes and Purchasing Intentions. The results found that Environmental Knowledge has a positive and significant impact on Attitudes and Purchasing Intentions. The results of the study found that Attitude has a positive and significant impact on Purchasing Intention.